Block Abstraction Memoization for CPAchecker - Wonisch, Daniel (Proceedings of the 18th International Conference on Tools and Algorithms for the Construction and Analysis of Systems (TACAS))
Block Abstraction Memoization (ABM) is a technique in software model checking that exploits the modularity of programs during verification by caching. To this end, ABM records the results of block analyses and reuses them if possible when revisiting the same block again. In this paper we present an implementation of ABM into the predicate-analysis component of the software-verification framework CPAchecker. With our participation at the Competition on Software Verification we aim at providing evidence that ABM can not only substantially increase the efficiency of predicate analysis but also enables verification of a wider range of programs.